Fast determination of aldehyde preservatives by miniaturized capillary electrophoresis with amperometric detection. Issue 2 (14th October 2013) - Li, Ying; Chen, Fang; Ge, Jinyuan; Tong, Fanghong; Deng, Zhaoyue; Shen, Fengwu; Gu, Qianxia; Ye, Jiannong; Chu, Qingcui; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> A novel miniaturized CE with amperometric detection (mini‐CE‐AD) method has been developed for fast determination of aliphatic aldehyde preservatives, namely formaldehyde and glyoxal, in commodities. After derivatization with an electroactive compound 2‐thiobarbituric acid, these two nonelectroactive aldehydes were converted to electroactive adducts, therefore detectable by mini‐CE‐AD approach. Under the optimum conditions, two aldehydes can be well‐separated with the coexisting interferents as well as their homologs (acetaldehyde and methyl‐glyoxal), and the LODs (S/N = 3) were achieved at nanogram‐per‐milliliter level (1.64–2.80 ng/mL) based on the online enrichment method of transient moving chemical reaction boundary. The proposed method has been applied for the analyses of above aldehyde preservatives in different real commodity samples including skincare products, baby lotion, and toothpaste, and the average recoveries were in the range of 94–105%, which should find a wide range of analytical applications as an alternative to conventional and microchip CE approaches.